2017
DOI: 10.21834/e-bpj.v2i5.708
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the Roles of Streets towards Improving Urban Quality of Life

Abstract: This conceptual paper aims to demystify how the quality of streets could facilitate the street culture and shaping greater urban qualities. Numerous scholars believed that certain streets had contributed an utmost factor in shaping man's civilisation. The development of modern cities has contributed to a great loss of streets significance as spaces for socialising and dwelling in the local peoples' needs. The outcome of this paper is hoping to guide the practitioners, policy makers and urban designers to incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A well-designed streetscape leads to a better quality of life. Designing visually pleasing urban streetscapes contributes to fostering desirable living environments, legible city images, and place identity (Ab Rahman et al, 2017).…”
Section: Physical Elements Of a Streetscapementioning
confidence: 99%
“…A well-designed streetscape leads to a better quality of life. Designing visually pleasing urban streetscapes contributes to fostering desirable living environments, legible city images, and place identity (Ab Rahman et al, 2017).…”
Section: Physical Elements Of a Streetscapementioning
confidence: 99%
“…With so many people living in such a small space, there is a traffic jam due to the lack of space for movement. Studies have shown that it is ideal for a city to have 30–35 % area for roads [ [27] , [28] , [29] ], whereas Dhaka city has only 8 % for roads [ 30 , 31 ] . Due to a lack of roads and proper infrastructure, Dhaka suffers an unreasonable traffic jam daily.…”
Section: Introductionmentioning
confidence: 99%